2023
DOI: 10.1590/1413-7054202347015122
|View full text |Cite
|
Sign up to set email alerts
|

Vernalization temperature and maturation point of seed cloves on garlic production and quality

Abstract: Brazilian producers have been seeking to improve garlic productivity and quality via vernalization at negative temperatures. However, more concrete information about the application and effects of this technique on the productivity and quality of noble garlic varieties is lacking. Moreover, there are also questions about the use and influence of seed cloves at different maturation points on this crop’s yield. Therefore, the objective of this work was to evaluate the effects of vernalization temperatures and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…These results indicate the potential of this technique, associated with sub-zero temperatures, to bring higher yields to the garlic crop in the study regions, with positive effects on the developmental characteristics and yield of the bulbs. Other authors have reported increased garlic production by treating the seed cloves below-zero temperatures [5,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicate the potential of this technique, associated with sub-zero temperatures, to bring higher yields to the garlic crop in the study regions, with positive effects on the developmental characteristics and yield of the bulbs. Other authors have reported increased garlic production by treating the seed cloves below-zero temperatures [5,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the productivity of garlic cultivated in São Miguel, observed in the treatments with negative temperatures, is equivalent to the average yield of garlic produced in the southern region, with productivity ranging from 4.5 to 9.8 kg ha −1 [2]. Luz et al [14] also obtained high productivity values with the Ito cultivar, applying temperatures below zero in the pre-planting treatment of seed cloves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations